2015
DOI: 10.1016/j.memsci.2015.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Co-ion fluxes of simple inorganic ions in electrodialysis metathesis and conventional electrodialysis

Abstract: a b s t r a c tThe main functionality of ion-exchange membranes is to selectively permeate either cations or anions. However, co-ions may permeate as well to some extent through these membranes. For the production of chemicals with electrodialysis metathesis and conventional electrodialysis, these co-ion fluxes are a major source of impurities in the produced chemicals. The present paper studies the co-ion fluxes and the influence of operating parameters. The results clearly indicate that co-ion fluxes are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Hence, it was reported that high voltage difference across the stack, sufficiently high feed concentration, equimolar ratio of reactant salts, high membrane transport number and moderate flow rate are critical parameters to obtain ideal operating conditions [ 144 , 145 , 146 , 147 , 148 , 149 ]. The difference in concentration across the membrane is also of particular importance, since it may result in co-ion fluxes leading to impurities in the final product; monovalent cations are especially subject to this phenomenon [ 150 ]. On another note, IEM characteristics strongly influence EDM performance.…”
Section: Recent Technological Developments Based On Ed Membrane Phmentioning
confidence: 99%
“…Hence, it was reported that high voltage difference across the stack, sufficiently high feed concentration, equimolar ratio of reactant salts, high membrane transport number and moderate flow rate are critical parameters to obtain ideal operating conditions [ 144 , 145 , 146 , 147 , 148 , 149 ]. The difference in concentration across the membrane is also of particular importance, since it may result in co-ion fluxes leading to impurities in the final product; monovalent cations are especially subject to this phenomenon [ 150 ]. On another note, IEM characteristics strongly influence EDM performance.…”
Section: Recent Technological Developments Based On Ed Membrane Phmentioning
confidence: 99%
“…To our knowledge, co-ions can theoretically be completely excluded from the polymer matrix in an ideal ion-exchange membrane. However, as a matter of fact, the selectivity of the ion exchange membrane cannot attain 100%, and some co-ions still exist in the membrane phase. Hence, the quantity of electric charge across the membrane includes that carried by counterions and co-ions.…”
Section: Development Of the Product Concentration Modelmentioning
confidence: 99%
“…Generally, membrane counterion transport number T represents the fraction of the current that is carried by counterions . The relationship between the membrane counterion transport number and ion transport number in Figure can be expressed as where T A and T S are the membrane counterion transport numbers of AEM and MAEM, respectively, ε K A is the K + transport number through AEM, and ε NH 4 S is the NH 4 + transport number through MAEM.…”
Section: Development Of the Product Concentration Modelmentioning
confidence: 99%
“…The rate of product formation can be controlled by applied current density which makes ED-M a safe route of synthesis. Concentration of products is limited by the rate of water transport, and product purity is limited by permselectivity of membranes and back diffusion, analogously to ED [22,23]. ED-M has the potential to be an energy and cost-effective intermediate synthesis step and reevaluation tool for highly soluble ionic compounds.…”
Section: Metathesis-electrodialysismentioning
confidence: 99%
“…The concentration of products was, however, limited by inevitable water transport, caused mostly by electroosmosis [81,82]. Purity of product is crucial for the application of final product and depends mostly on selectivity of membranes and composition of raw materials Unauthenticated Download Date | 5/11/18 5:27 AM [22,23]. The main advantage of applying ED-M to synthesis or conversion of inorganic salts is its non-equilibrium character which allows for using substrates that will lead to the co-precipitation of undesired products or formation of double salts when components are simply mixed together, as in conventional metathesis.…”
Section: Conversion Of Inorganic Saltsmentioning
confidence: 99%